Alterations in Nitric Oxide Synthase in the Aged CNS. (5th July 2012) - Jung, Junyang; Na, Changhyun; Huh, Youngbuhm
Abstract : Aging is associated with neuronal loss, gross weight reduction of the brain, and glial proliferation in the cortex, all of which lead to functional changes in the brain. It is known that oxidative stress is a critical factor in the pathogenesis of aging; additionally, growing evidence suggests that excessive nitric oxide (NO) production contributes to the aging process. However, it is still unclear how NO plays a role in the aging process. This paper describes age-related changes in the activity of NADPH-diaphorase (NADPH-d), a marker for neurons containing nitric oxide synthase (NOS), in many CNS regions. Understanding these changes may provide a novel perspective in identifying the aging mechanism.